Clinical Course of Coronary Heart Disease Concomitant with Asthma - N. Y. Grigoryeva; T. P. Ilyushina; K. S. Kolosova; N. B. Koroleva; A. A. Streltsova; D. V. Soloveva (SINAPS LLC, 2020)
The research purpose: to study features of clinical process of a coronary heart disease when it combines with a bronchial asthma.The materials and methods: 180 people were included in the research, 90 of them suffer from both CHD and BA (the first group), and also 90 people have only CHD without BA (the second group). The examination included complaint collection process, studying medical history, medical examination, percussion, auscultation, blood pressure measurement with the Korotkov's method twice a day (in the morning and in the evening), heart rate measurement, 24-hour Holter ECG monitoring, echodoplercardiography. Besides, standard laboratory biochemical testing, including total cholesterol and lowdensity lipoprotein cholesterol, were made with the enzymatic colorimetric method.The results. Dyspnoea is the main complaint among 86 patients with both CHD and asthma, humans have (95,5%), moreover, dyspnoea combines with heartbeating in 73,8%, and is accompanied by angina pectoris only in 20%. There is a significant difference between systolic and diastolic blood pressure (р=0,001) that becomes higher if CHD combines with asthma. The signs of left ventricular and interventricular septum hypertrophy were discovered in the first group, these signs statistically significantly differ from the ones in the second group. The medium pulmonary arterial pressure is significantly higher in the combined group than in the group with only CHD (р=0,001). It is revealed with 24-hour Holter ECG monitoring that cases of myocardial ischemia are more frequent in the group which consists of patients with CHD. Besides, duration of ischemic depression per day is longer in this group too. It might be that if patients have both CHD and asthma they do not reach an ischemic threshold because of dyspnoea due to a respiratory failure.The conclusion. According to our findings bronchial asthma occurs among patients with coronary heart disease in 16.6% of cases. It is a distinctive feature of a bronchial asthma associated with coronary heart disease, that a patient often complaints to dyspnea (cardiopulmonary) and palpitation, increase in arterial blood pressure and heart rate, which appropriately indicates the activation of rennin-angiotensin-aldosteron and sympathicoadrenal systems. It requires the inclusion of appropriate drug groups in the treatment of patients.